2016
DOI: 10.1080/15476278.2016.1229726
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 suppresses osteogenic differentiation of periodontal ligament stem cells through inactivation of mitogen-activated protein kinase pathway

Abstract: ABSTRACT. Periodontal ligament stem cells (PDLSCs) are tissue-specific mesenchymal stem cells (MSCs), having an important role in regenerative therapy for teeth loss. Interleukin-7 (IL-7) is a key cytokine produced by stromal cells including MSCs, and exhibits specific roles for B and T cell development and osteoblasts differentiation of multiple myeloma. However, the effect of IL-7 on osteogenic differentiation of PDLSCs remains unclear. Therefore, in the present study we determined whether IL-7 affects the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Several studies have confirmed that p38 MAPK and JNK are positive regulators of osteogenic differentiation. 56,57 For example, BMP2 induces osteoblastic cell differentiation via activation of the p38 MAPK and JNK pathways. 58 Periostin promotes the osteogenic differentiation potential of PDLSCs through the JNK pathway under inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that p38 MAPK and JNK are positive regulators of osteogenic differentiation. 56,57 For example, BMP2 induces osteoblastic cell differentiation via activation of the p38 MAPK and JNK pathways. 58 Periostin promotes the osteogenic differentiation potential of PDLSCs through the JNK pathway under inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed 11 genes that are related to osteoblast differentiation and bone development by qPCR. The upregulated genes ( Trp63 , Fbn2 , Sfrp2 , Adamts12, and Eya1 ) are all positive regulators of osteoblast differentiation ( Cho et al., 2008 , Ji et al., 2016 , Nistala et al., 2010 , Sworder et al., 2015 , Yang et al., 1999 ), and the downregulated genes ( Hes1 , Wnt9a , Syk, Comp, IL-7, and Nox4 ) are negatively impacted in osteoblast differentiation ( Guo et al., 2014 , Jian et al., 2016 , Mandal et al., 2011 , Yoshida et al., 2011 , Zhang et al., 2009 , Zhou et al., 2009 ). These altered genes may cooperate to contribute the enhanced osteoblast differentiation potential in Tet2 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that direct injection of IL-7 in mice inhibits bone formation [ 105 ]. In periodontal ligament stem cells, IL-7 suppresses osteoblastogenesis by downregulating osteoblastogenic markers, such as RUNX2, OSX, ALP, and OCN, through the inactivation of the MAPK pathway [ 106 ]. In multiple myeloma, IL-7 is implicated in inhibiting bone formation by suppressing RUNX2 activity [ 107 ].…”
Section: Cytokine Regulation Of Osteoblastogenesismentioning
confidence: 99%